Nurses' knowledge, perceptions, and behaviors regarding antineoplastic drugs: the mediating role of protective knowledge† - Liu Ning; Lu Hong; Yi Xiao-Qing; Yang Yang; Huang Xiao-Hong (Sciendo, 2022)
To explore the relationships between Chinese nurses' knowledge, perceptions, and attitudes and their behavior and actual implementation of safety measures when handling antineoplastic drugs (ADs) in their daily work.